2008
DOI: 10.1104/pp.108.123844
|View full text |Cite
|
Sign up to set email alerts
|

AtPTR1 and AtPTR5 Transport Dipeptides in Planta

Abstract: Transporters for di-and tripeptides belong to the large and poorly characterized PTR/NRT1 (peptide transporter/nitrate transporter 1) family. A new member of this gene family, AtPTR5, was isolated from Arabidopsis (Arabidopsis thaliana). Expression of AtPTR5 was analyzed and compared with tissue specificity of the closely related AtPTR1 to discern their roles in planta. Both transporters facilitate transport of dipeptides with high affinity and are localized at the plasma membrane. Mutants, double mutants, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(141 citation statements)
references
References 68 publications
1
138
0
Order By: Relevance
“…Furthermore, the calculated K m of EnvFOT-Fp for Tyr-Ala (23 mM) is lower than affinity constants reported for plant peptide transporters of the peptide transport family as estimated using Xenopus oocytes (for example, 130-160 mM for the root-expressed AtPTR5; Komarova et al, 2008, and references therein). As for the concentration of di/tripeptides in the soil solution, no quantitative data are available to our knowledge.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, the calculated K m of EnvFOT-Fp for Tyr-Ala (23 mM) is lower than affinity constants reported for plant peptide transporters of the peptide transport family as estimated using Xenopus oocytes (for example, 130-160 mM for the root-expressed AtPTR5; Komarova et al, 2008, and references therein). As for the concentration of di/tripeptides in the soil solution, no quantitative data are available to our knowledge.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, heterologous expression in Xenopus oocytes allowed us to demonstrate that at least EnvFOT-F could transport L-cysteine. The transport of additional nitrogenous compounds had already been documented for other eukaryotic di/tripeptide transporters such as the yeast dal5p known to transport allantoate and ureidosuccinate (Cai et al, 2007), the Arabidopsis PTR2-B and PTR1 shown to transport histidine (Frommer et al, 1994;Komarova et al, 2008) and the human hPAT1 that transports both amino acids and a few dipeptides (Frølund et al, 2010). It is therefore possible that the true range of N compounds transported by FOT transporters extends beyond di/tripeptides and cysteine.…”
Section: Discussionmentioning
confidence: 99%
“…As inferred from the transcriptional activation of the corresponding genes in cells containing arbuscules (Table S3), both MtPTR1 and MtSPT13 are likely to have a role at this symbiotic interface. According to characterization of the PMlocalized PTR1 in Arabidopsis (Komorova et al 2008(Komorova et al , 2012, MtPTR1 may function as a di-and tripeptide transporter. Noticeably, the putative dipeptide transporter RiPTR2 has been identified in R. irregularis (Belmondo et al 2014).…”
Section: Am-responsive Proteins As Related To Sugar/peptide Transportmentioning
confidence: 99%
“…Although small peptides (e.g., DPs and tripeptides) are considered as a nitrogen source for plant growth, data regarding these molecules, their abundance, and their roles in plants are limited (25). Nontargeted analysis of extracts derived from the five sorted cell-type populations suggested the accumulation of DPs in specific cell types.…”
Section: Moussaieff Et Al Pnas | Published Online March 8 2013 | E1mentioning
confidence: 99%